Whole Y-chromosome sequences reveal an extremely recent origin of the most common North African paternal lineage E-M183 (M81). Issue 1 (December 2017) - Solé-Morata, Neus; García-Fernández, Carla; Urasin, Vadim; Bekada, Asmahan; Fadhlaoui-Zid, Karima; Zalloua, Pierre; Comas, David; Calafell, Francesc
Abstract E-M183 (E-M81) is the most frequent paternal lineage in North Africa and thus it must be considered to explore past historical and demographical processes. Here, by using whole Y chromosome sequences from 32 North African individuals, we have identified five new branches within E-M183. The validation of these variants in more than 200 North African samples, from which we also have information of 13 Y-STRs, has revealed a strong resemblance among E-M183 Y-STR haplotypes that pointed to a rapid expansion of this haplogroup. Moreover, for the first time, by using both SNP and STR data, we have provided updated estimates of the times-to-the-most-recent-common-ancestor (TMRCA) for E-M183, which evidenced an extremely recent origin of this haplogroup (2, 000–3, 000 ya). Our results also showed a lack of population structure within the E-M183 branch, which could be explained by the recent and rapid expansion of this haplogroup. In spite of a reduction in STR heterozygosity towards the West, which would point to an origin in the Near East, ancient DNA evidence together with our TMRCA estimates point to a local origin of E-M183 in NW Africa.